PEMBANGUNAN BERKELANJUTAN DI KABUPATEN SIAK (STUDI KASUS PENGENDALIAN ALIH FUNGSI LAHAN SAWAH KE SAWIT) - Galuh Widya Oktaviani; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study discusses the form of Sustainable Development in Siak Regency (Case Study of Controlling the Transfer of Rice Fields to Oil Palm). Protection of sustainable food agricultural land is a system and process in planning and establishing, developing, utilizing and fostering, controlling, and monitoring food agricultural land and its area continuously. The purpose of this study was to determine how Sustainable Development in Siak Regency (Case Study of Controlling the Transfer of Rice Fields to Oil Palm) and the inhibiting factors of Sustainable Development in Siak Regency (Case Study of Controlling the Transfer of Rice Fields to Oil Palm). This research method is atype of qualitative research, the selection of informants using purposive techniques and snowball sampling. Data collection techniques are through observation, interviews and documentation. The result of the study indicate that Sustainable Development in Siak Regency (Case Study of Controlling the Transfer of Rice Fields to Palm Oil) has not been implemented optimally, with no standard operating proceduders set yet. The inhibiting factors include human resource managers, public awareness is still lacking and facilities and infrastucture.                                                                                                                          Keywords: Control, Function Transfer, Sustainable Development